A neglected treatment in middle school and high school age genital trauma: analgesia management with pain scoring - Abuzer Coşkun; Çilem Çaltılı; Burak Demirci (Cukurova Medical Journal, 2022)
Purpose: The purpose of this study was to assess analgesic applications accompanied by numerical and verbal pain scores, radiological imaging, and consultation requests for genital traumas, which affect a small percentage of middle and high school students. Materials and Methods: This retrospective study included 237 middle school and high school age, 10-18 years old patients who applied to the emergency department due to genital trauma between January 2019 and December 2020. The types of trauma, radiological imaging, genital organ injuries, analgesia applications, consultations, and verbal and numerical pain scale scores of patients were all evaluated. Results: Of the 237 patients included in the study, 90 (38%) were female, and the mean age was 13.80±2.37 years (range, 10-18 years). Of the patients, 136(57.4%) were admitted with falls, 63(26.6%) traffic accidents, 35(14.8%) penetrating and 3(1.3%) iatrogenic injuries. The numerical pain score was 6.63±1.43 in falls, 6.09±1.66 in traffic accidents, 4.80±1.53 in penetrating injuries, and 3.67±1.15 in iatrogenic traumas. Analgesics were administered to 93(39.2%) of all patients. The severity of pain was mild in 43(18.1%) patients. It was moderate in 140(59.1%) and severe in 54(22.8%). Conclusion: Genital traumas that occur alone are extremely rare and are frequently associated with multiple organ injuries. Genital traumas have a wide variety of etiological causes and complications. In cases of pediatric genital trauma, the use of verbal and numerical pain scales may be beneficial in evaluating patients, determining imaging requirements, and determining analgesia applications.